Loss of age-accumulated crh-1 circRNAs ameliorate amyloid β-induced toxicity in a C. elegans model for Alzheimer’s disease - Alshareef, Hussam Z.; Ballinger, Thomas; Rojas, Everett; van der Linden, Alexander M. (Frontiers in Aging Neuroscience, 2025)
Circular RNAs (circRNAs) are non-coding RNAs mostly derived from exons of protein-coding genes via a back-splicing process. The expression of hundreds of circRNAs accumulates during healthy aging and is associated with Alzheimer’s disease (AD), which is characterized by the accumulation of amyloid-beta (Aβ) proteins. In C. elegans, many circRNAs were previously found to accumulate during aging, with loss of age-accumulated circRNAs derived from the CREB gene (circ-crh-1) to increase mean lifespan. Here, we used C. elegans to study the effects of age-accumulated circRNAs on the age-related onset of Aβ-toxicity. We found that circ-crh-1 mutations delayed Aβ-induced muscle paralysis and lifespan phenotypes in a transgenic C. elegans strain expressing a full-length human Aβ-peptide (Aβ1–42) selectively in muscle cells (GMC101). The delayed Aβ phenotypic defects were associated with the inhibition of Aβ aggregate deposition, and thus, genetic removal of circ-crh-1 alleviated Aβ-induced toxicity. Consistent with a detrimental role for age-accumulated circRNAs in AD, the expression level of circ-crh-1 expression is elevated after induction of Aβ during aging, whereas linear crh-1 mRNA expression remains unchanged. Finally, we found that the delayed onset of Aβ-induced paralysis observed in circ-crh-1 mutants is dependent on the col-49 collagen gene. Taken together, our results show that the loss of an age-accumulated circRNA exerts a protective role on Aβ-induced toxicity, demonstrating the utility of C. elegans for studying circRNAs in AD and its relationship to aging.